2009
DOI: 10.1093/bioinformatics/btp551
|View full text |Cite
|
Sign up to set email alerts
|

How and when should interactome-derived clusters be used to predict functional modules and protein function?

Abstract: Motivation: Clustering of protein–protein interaction networks is one of the most common approaches for predicting functional modules, protein complexes and protein functions. But, how well does clustering perform at these tasks?Results: We develop a general framework to assess how well computationally derived clusters in physical interactomes overlap functional modules derived via the Gene Ontology (GO). Using this framework, we evaluate six diverse network clustering algorithms using Saccharomyces cerevisiae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 41 publications
4
125
0
Order By: Relevance
“…Protein products of the connecting genes also form a protein-protein interaction network with a higher connectivity than randomized versions of the same network (clustering coefficient=0.27 versus 0.09, P=0.01), which suggests a strong functional interconnection of the encoded proteins (which has previously been shown for Saccharomyces cerevisiae) 13 (Supplemental Figure 1).…”
Section: Association Of Pathway Network With Ckdsupporting
confidence: 58%
“…Protein products of the connecting genes also form a protein-protein interaction network with a higher connectivity than randomized versions of the same network (clustering coefficient=0.27 versus 0.09, P=0.01), which suggests a strong functional interconnection of the encoded proteins (which has previously been shown for Saccharomyces cerevisiae) 13 (Supplemental Figure 1).…”
Section: Association Of Pathway Network With Ckdsupporting
confidence: 58%
“…Only recently has this method been applied to the study of protein complexes using label-free AP-QMS strategies (32,33,38) with multiple baits. Various strategies and algorithms have been developed for network topology analysis that have been evaluated and reviewed in detail elsewhere (103)(104)(105). Nevertheless, most of the strategies use co-purification profiles to assign pairwise interaction scores and/or probabilistic measurements to group proteins into three main topological clusters: cores, modules, and attachments (103)(104)(105)(106)(107)(108).…”
Section: Protein-protein Interaction (Ppi) Network Analysis and Functmentioning
confidence: 99%
“…Various strategies and algorithms have been developed for network topology analysis that have been evaluated and reviewed in detail elsewhere (103)(104)(105). Nevertheless, most of the strategies use co-purification profiles to assign pairwise interaction scores and/or probabilistic measurements to group proteins into three main topological clusters: cores, modules, and attachments (103)(104)(105)(106)(107)(108). Core proteins stably associate and stoichiometrically co-purify with every protein complex subunit.…”
Section: Protein-protein Interaction (Ppi) Network Analysis and Functmentioning
confidence: 99%
“…Even with the proposed null model for multiprotein modules, biological process enrichment may retain limitations as a measure of biological meaning. Studies have shown that biological process enrichment tends to be an optimistic measure, with many multiprotein modules, even those unreasonable by other measures, often deemed significant (5,21). This problem is at least partially addressed by the improved null model presented in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Subtracting a baseline value averaged over randomly generated modules of the desired size corrects for much of this optimism. An alternative measure of biological meaning is semantic density (21), which can also be normalized by module size. It would be interesting to see whether the general trends observed with biological process enrichment hold for semantic density and other measures of biological meaning.…”
Section: Discussionmentioning
confidence: 99%